Evolution of the exclusively human pathogen Neisseria gonorrhoeae: Human‐specific engagement of immunoregulatory Siglecs. (3rd January 2019) - Landig, Corinna S.; Hazel, Ashley; Kellman, Benjamin P.; Fong, Jerry J.; Schwarz, Flavio; Agarwal, Sarika; Varki, Nissi; Massari, Paola; Lewis, Nathan E.; Ram, Sanjay; Varki, Ajit
Abstract: Neisseria gonorrhoeae causes the sexually transmitted disease gonorrhea exclusively in humans and uses multiple strategies to infect, including acquisition of host sialic acids that cap and mask lipooligosaccharide termini, while restricting complement activation. We hypothesized that gonococci selectively target human anti‐inflammatory sialic acid‐recognizing Siglec receptors on innate immune cells to blunt host responses and that pro‐inflammatory Siglecs and SIGLEC pseudogene polymorphisms represent host evolutionary adaptations to counteract this interaction. N. gonorrhoeae can indeed engage multiple human but not chimpanzee CD33rSiglecs expressed on innate immune cells and in the genitourinary tract––including Siglec‐11 (inhibitory) and Siglec‐16 (activating), which we detected for the first time on human cervical epithelium. Surprisingly, in addition to LOS sialic acid, we found that gonococcal porin (PorB) mediated binding to multiple Siglecs. PorB also bound preferentially to human Siglecs and not chimpanzee orthologs, modulating host immune reactions in a human‐specific manner. Lastly, we studied the distribution of null SIGLEC polymorphisms in a Namibian cohort with a high prevalence of gonorrhea and found that uninfected women preferentially harbor functional SIGLEC16 alleles encoding an activating immune receptor. These results contribute to the understanding of the human specificity of N. gonorrhoeae and how it evolved to evade the human immune defense.